PRIBADI MUSLIMAH DALAM NOVEL PINGKAN SEHANGAT MENTARI MUSIM SEMI KARYA MUTHMAINNAH: PERSPEKTIF FEMINISME ISLAM - Rusdian Noor Dermawan (CARAKA, 2015)
The Objective of this research are to describe (1) character and characterization of woman Moslem Pingkan with her setting, (2) problems faced by the character in international communication in Australia, (3) the ways done by Pingkan in facing the problems in international communication, and (4) feminism ideology believed and applied by Pingkan character in the Pingkan Sehangat Mentari Musim Semi novel. The type of the research is descriptive qualitative. The form of data is unity event concerned with the research question found in the Pingkan Sehangat Mentari Musim Semi novel, while the source of the data is the novel itself. The research instruments are text and the researcher equipped with a set of concepts needed to answer the problem formulation. Data are collected by observation technique, while the data analysis technique applied is descriptive qualitative analysis technique. The result of the research is as follows. The main character of Pingkan Sehangat Mentari Musim Semi novel is Pingkan Rahma because her thought, attitude, and behavior connected each other with the theme of the novel, having the most interaction with other characters, and need much time to tell her story, as a loyal Moslem woman. Pingkan has an autonomous personal, optimistic, surrender to Allah SWT, shalihah, firm, rationalistic, courage, spoiled, helper, wide thought, critics, stiff, diligent, positive thinking, funny, honest, and feministic. The main place setting is in Australia, the time setting is at the end of a new era, while the social setting is described as an individual, liberal, heterogenous, and racial society. The problems of communicating using English is solved by Pingkan with increasing direct communication to Tom and Berth. The problem of free sex is solved by drawing near to Allah, the lack of a place to pray is solved by seeking room but pure, the heterogenous problem is solved by tolerance, attention, and empathy to other people, the problem of feminism demonstration is solved by reject through oration and discussion. Based on her feminism view, it shows clearly that Pingkan is a feminism Moslem.